A Comprehensive Study on the Associativity of T2DM and Cognitive Impairment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
T2DM and cognition disability are also very common diseases around the world. While the diabetes of variant type 2 is linked to an increased incidence of dementia, there is little understanding of the correlation between the two conditions, and Clinicians can be guided little by recommendations for treating cognitive disability in diabetes patients. A body of corroborationmanifestate that insulin resistance, root cause for diabetes, also plays a major ramification in Alzheimer's disease.Diabetic lifestyle awareness and risk management are important to prevent cognitive issues. This paper provides a comprehensive study of diabetes' relationship with cognitive dysfunction, and also the emerging approaches are essential to both identification and treatment, and control as well as cognitive disabilities in those with diabetes. Significant associations were found in the T2D-MCI population between memory and insulin medication (immediate recall), complicated figure copy, and attention.This case-control study investigated an association between the form of diabetes known as type 2 and minor cognitive impairment, and the prevalence in non-diabetics and type 2 diabetics of mild cognitive impairment. There is a conceptual framework to deal with screening and treatment and future research guidelines to guide the field.